Minori Stranieri Non Accompagnati: quale diritto alla famiglia? Esiti da una ricerca qualitativa nella Regione Emilia-Romagna - Lorenzini, Stefania (Rivista Italiana di Educazione Familiare, 2019)
This contribution offers a reflection on the right to family and the familiar links of Unaccompanied Foreign Minors. In the central part of the article, we focus on qualitative research outcome, in order to deep some aspects of the educational activities implemented within the second level communities welcoming minors, in the context of Emilia-Romagna region. Specifically, we consider the relationships that young people in the communities are able to entertain with members of the families of origin, remained in the countries of birth, according to what is known and narrated by educators and community leaders, interviewed in the context of the research carried out in the first months of 2017.